Biological activities of extracts and isolated compounds from Bauhinia galpinii (Fabaceae) and Combretum vendae (Combretaceae) as potential antidiarrhoeal agents - Eloff, Jacobus Nicolaas (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2013.